Institutional Model-Based Community Economic Development In The District Indramayu - Warcito, Warcito (Jurnal Manajemen, 2018)
The purpose of this study was (1) Identify the potential and the problems faced by the target group KIMBis in science and technology-based community economic development, (2) Increase the capacity of businesses through technology escort KIMBis target group, and (3) Build the institutional model description based community economic development science and technology. The approach taken in this study in the form of action research. Implementation of applied research carried out in the form of activities in the village KIMBis Kandanghaur Eretan Wetan District of Indramayu district. The results of this study showed that (a) Clinical Technology Business Mina in Indramayu formed based on the potential of fisheries resources and aquaculture (b) Institutional KIMBis Indramayu become media for awareness stage, and shuck pengkapasitasan target groups involving many stakeholders. (c) may receive a referral Indramayu KIMBIs institutional model of community-based economic development of science and technology.